A Methods engineering study on Videxco Corporation - Blanco, Mariel (College of Engineering, 1999)
Videxco corporation is a garments manufacturing corporation that produces quality clothes for distribution nationwide. A medium scale enterprise, the company is an appropriate choice for this study. The aim of this study is to utilize the Method Engineering tools covered by the course to fully document existing systems, analyze relevant problem areas, and provide recommendations to the company regarding these problem areas. After thorough observations and documentation, the study identified three main problems of the company : ineffective systems and procedures, no standard method of sewing, and poor plant layout. Interviews were conducted and observations were made during the plant visits for the documentation of the company's systems and procedures. The study is recommending the use of standard forms to aid the effectivity of information flow within the company. A time study was conducted to measure performance of the sewers. The average basic times were used to compute for theoretical averages using the Learning Curve theory. These averages were then compared to actual averages. The study has shown that based on the learning curve theory, the recommended method of sewing by parts is more efficient than the present method of per piece sewing. Using flow diagrams, the study was able to show backtracking that occurs with the flow of man and materials during the production process. A change in layout is proposed to eliminate backtracking. Also, the sewing area was seen to be lacking in proper storage facilities for work in process. An alternative layout for the sewing department was also recommended.